Pengaruh Penyuluhan Kesehatan terhadap Tingkat Pengetahuan dan Pola Makan untuk Mencegah Gastrisitas pada Remaja di SMAN 2 Kendari Tahun 2024 - Andi Kumala; Wa Ode Salma; Harleli Harleli (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2024)
Gastritis is an inflammation of the stomach lining that frequently affects adolescents due to unhealthy eating habits, stress, and poor lifestyle choices, with a significant global prevalence, such as 40.8% in Indonesia, according to WHO data from 2021. In Kendari City, the incidence of gastritis has increased from 4,856 cases (1.23%) in 2019 to 7,846 cases (2.24%) in 2022, with adolescent cases at Poasia Health Center reaching 14.8% in 2022. Health education has proven effective in increasing adolescents' knowledge about gastritis prevention, helping them understand the importance of healthy eating habits, and encouraging behavioral changes to reduce gastritis prevalence in the future. The purpose of this study is to determine the effect of nutrition education on knowledge levels and eating habits to prevent gastritis among adolescents at SMAN 2 Kendari in 2023. This research employs a Quasi-Experimental design with a Pre-test Post-test Non-Equivalent Control Group Design. The sample size consists of 84 students selected using purposive sampling. The study results indicate that the Wilcoxon signed-rank test for knowledge and eating habits data shows a p-value of 0.000 ≤ 0.05, which is significant. Based on these findings, it can be concluded that health education significantly influences knowledge levels and eating habits in preventing gastritis among adolescents at SMAN 2 Kendari in 2024. This study is expected to provide input for research sites, health services, parents, adolescents, and other researchers to enhance knowledge, awareness, and healthy eating habits in preventing gastritis through health promotion and further research development